2017
DOI: 10.1093/jxb/erx170
|View full text |Cite
|
Sign up to set email alerts
|

CBL-interacting protein kinase 6 negatively regulates immune response to Pseudomonas syringae in Arabidopsis

Abstract: CBL-interacting protein kinase 6 (CIPK6) negatively regulates the PAMP-triggered and effector-triggered immune response in Arabidopsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 66 publications
0
33
0
Order By: Relevance
“…Ca 2+ signalling has a regulatory effect on HR induced by P. triticina infection (Guan et al , 2006), and an extracellular calcium influx to the cell was shown to be a major source of calcium signalling (Liu et al , 2010). Plants overexpressing CBL‐interacting protein kinase 6 negatively regulate immunity and were more susceptible to Pseudomonas syringae in Arabidopsis (Sardar et al , 2017). Wheat calcium‐dependent protein kinase TaCPK7‐D overexpression activates defence‐related genes, leading to enhanced resistance to sharp eyespot caused by Rhizoctonia cerealis , and positively regulates host resistance to sharp eyespot disease (Wei et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ signalling has a regulatory effect on HR induced by P. triticina infection (Guan et al , 2006), and an extracellular calcium influx to the cell was shown to be a major source of calcium signalling (Liu et al , 2010). Plants overexpressing CBL‐interacting protein kinase 6 negatively regulate immunity and were more susceptible to Pseudomonas syringae in Arabidopsis (Sardar et al , 2017). Wheat calcium‐dependent protein kinase TaCPK7‐D overexpression activates defence‐related genes, leading to enhanced resistance to sharp eyespot caused by Rhizoctonia cerealis , and positively regulates host resistance to sharp eyespot disease (Wei et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis AtCIPK6 negatively regulates ROS production in ETI and PTI. Atcipk6 loss-of-function mutant plants possess more resistance to Pseudomonas syringae, but overexpression lines are more susceptible [170]. In rice, OsCIPK14 and the duplicated gene OsCIPK15 are rapidly induced by MAMPs, and their proteins interact with OsCBL4.…”
Section: The Cbl-cipk Network In Biotic Stressmentioning
confidence: 99%
“…In the majority of cases CBLs are interact with CIPKs (CBL-interacting protein kinases) and regulate diverse functions including abscisic acid signaling and salt tolerance and [61,62]. The CIPKs which are the major interacting partner of CBLs are involved in immune response, response to salt, osmotic and abscisic acid stress, plant growth and development [61,62,63]. Wheat CIPK 25 is negatively regulate salt tolerance in the transgenic wheat [64].…”
Section: Interactome Map Of Cams Cmls Cbls and Cdpksmentioning
confidence: 99%